Housing Finance in Sri Lanka : Opportunities and Challenges - World Bank (Washington, DC, 2012)
Sri Lanka has embarked on a gradual transition from a system of directed credit in a highly segmented market toward an integrated market-driven housing finance system. This transition has included an increased role of private universal banks in the immediate term and a functioning secondary mortgage market in the long term. An active system of housing finance provides real economic benefits and positively affects savings, investment, and household wealth. It provides an investment option for long-term funds in the economy as an alternative to investment in treasury bonds. In turn, each dollar invested in the housing sector catalyzes economic activity in other sectors, exerting an indirect positive impact on employment levels, the retirement system, fiscal returns, and consumption. Housing finance enables households to accumulate assets that can provide the collateral for their investment needs, thus stimulating small business. Housing finance development boosts equitable economic growth and reduces poverty by improving living conditions, empowering the middle and lower-income population, and strengthening communities. Housing policy focuses on improving government land use and maximizing the use of the existing housing stock by providing basic public services and upgrades.